SKETCH OF INTERTEXTUALITY OF TEXTS WITH ISLAMIC DISCOURSES IN TRADITIONAL BALINESE LITERATURE - Jelantik SP, Ida Bagus; Kutha Ratna, Nyoman; Suarka, I Nyoman; Weda Kusuma, I Nyoman (e-Journal of Linguistics, 2014)
Researchers have identified the existence of Islamic discourses in the texts of the traditional Bali literature since a long time ago; however, attention has not been properly paid to them. It has been identified that a number of oral texts ( kesusastraan gantian ) in the forms of poem and prose contain Islamic discourses. Likewise, a number of written texts in the form of manuscripts ( kesusastraan sasuratan ) have also been identified to contain the same literary genre. Historically, the texts containing Islamic discourses in the traditional Balinese literature belong to the Old Balinese literature ( kesusastraan Bali purwa) rather than the Modern Balinese literature ( kesusastraan Bali anyar ). The most striking phenomenon in the existence of the texts of Islamic discourses in the traditional Balinese literature is their relationship to other texts. Explicitly, several texts in their manuscripts direct their readers in such a way that they will consider them related to other texts. In other words, the texts with Islamic discourses in the traditional Balinese literature are the transformed ones reflecting the fact of intertextuality. This present study was intended to give a general picture of the intertextual relationship of the texts with Islamic discourses to other texts; their relationship to the texts within the discursive scope of the Balinese culture and the other texts which belong to the treasures of the traditional Javanese literature and the Old Malay literature.
Keywords: Islamic discourse, transformational, intertextuality